SYNTACTIC AMBIGUITY FOUND IN BUSINESS HEADLINES OF THE NEW YORK TIMES - Siti Nurfadilah (EL2J (English Language and Literature Journal), 2022)
This study is conducted to analyze the syntactic ambiguity in business headlines on the news of The New York Times. This study aimed at explaining: (1) the ambiguity in the tree diagram. (2) The suitability of the headlines with the content of the news in The New York Times. The data source is the online news in The New York Times. The data are collected by (1)Opening the Google Chrome app, (2) Accessing the official website https://nytimes.com, (3) Choosing the column "business", (4) Collecting headlines via copy and paste and screenshotting news content in a word document, (5) Writing the ten data of headlines into the table, (6) Coding the data, while the procedure of data analysis are: (1) Reading the headlines, (2) Drawing the tree diagrams, (3) Describing the meaning, (3) Interpreting the data, (4) Drawing conclusion. In this research, the writer concluded that ambiguous headlines are represented in tree diagrams based on syntax categories, namely parts of speech and phrases. Also, there are nine news headlines that are in accordance with the news content and one headline that is not in accordance with the news content.